A class of conserved surface layer integrals for causal variational principles - Finster, Felix; Kleiner, Johannes (Calculus of variations and partial differential equations, 2019)
In the theory of causal fermion systems, the physical equations are obtained as the Euler–Lagrange equations of a causal variational principle. Studying families of critical measures of causal variational principles, a class of conserved surface layer integrals is found and analyzed.